Comparison of mechanical disturbance in soft sediments due to tickler-chain SumWing trawl vs. electro-fitted PulseWing trawl. (20th September 2018) - Depestele, Jochen; Degrendele, Koen; Esmaeili, Moosa; Ivanović, Ana; Kröger, Silke; O'Neill, Finbarr G; Parker, Ruth; Polet, Hans; Roche, Marc; Teal, Lorna R; Vanelslander, Bart; Rijnsdorp, Adriaan D
Abstract: Tickler-chain SumWing and electrode-fitted PulseWing trawls were compared to assess seabed impacts. Multi-beam echo sounder (MBES) bathymetry confirmed that the SumWing trawl tracks were consistently and uniformly deepened to 1.5 cm depth in contrast to 0.7 cm following PulseWing trawling. MBES backscatter strength analysis showed that SumWing trawls (3.11 dB) flattened seabed roughness significantly more than PulseWing trawls (2.37 dB). Sediment Profile Imagery (SPI) showed that SumWing trawls (mean, SD) homogenised the sediment deeper (3.4 cm, 0.9 cm) and removed more of the oxidised layer than PulseWing trawls (1 cm, 0.8 cm). The reduced PulseWing trawling impacts allowed a faster re-establishment of the oxidised layer and micro-topography. Particle size analysis suggested that SumWing trawls injected finer particles into the deeper sediment layers (∼4 cm depth), while PulseWing trawling only caused coarsening of the top layers (winnowing effect). Total penetration depth (mean, SD) of the SumWing trawls (4.1 cm, 0.9 cm) and PulseWing trawls (1.8 cm, 0.8 cm) was estimated by the depth of the disturbance layer and the layer of mobilized sediment (SumWing = 0.7 cm; PulseWing trawl = 0.8 cm). PulseWing trawls reduced most of the mechanical seabed impacts compared to SumWing trawls for this substrate and area characteristics.